Complementary Specializations of the Left and Right Sides of the Honeybee Brain - Rogers, Lesley J.; Vallortigara, Giorgio (Frontiers in Psychology, 2019)
Honeybees show lateral asymmetry in both learning about odours associated with reward and recalling memory of these associations. We have extended this research to show that bees exhibit lateral biases in their initial response to odours: viz., turning towards the source of an odour presented on their right side and turning away from it when presented on their left side. The odours we presented were the main component of the alarm pheromone, iso-amyl acetate (IAA), and four floral scents. The significant bias to turn towards IAA odour on the right and away from it on the left is, we argue, a lateralization of the fight-flight response elicited by this pheromone. It contrasts to an absence of any asymmetry in the turning response to an odour of the flowers on which the bees had been feeding prior to testing: to this odour they turned towards when it was presented on either the left or right side. Lemon and orange odours were responded to differently on the left and right sides (towards on the right, away on the left) but no asymmetry was found in responses to rose odour. Our results show that side biases are present even in the initial, orienting response of bees to certain odours.